Holistic approach to the vocational counselling of students with special education needs - Ingrida Baranauskienė; Liuda Radzevičienė; Aistė Valaikienė; Joanna Kossewska (Social Welfare: Interdisciplinary Approach, 2012)
Vocational counselling is the first and one of the most important stages of prevocational education of pupils with SEN that has influence on successful integration into the labour market and human socialization. In the article the parameters of the ideal model of vocational counselling of pupils with SEN have been analyzed. In identifying the criteria of vocational counselling of pupils with SEN it has been referred to the model of systemic analysis constructed by Le Moigne, described by Baranauskienė, Juodraitis (2008), and in which 5 approaches towards successful participation of persons with disabilities in the labour market have been singled out: approaches towards success from the aspect of structure, aims, influence of environment, development, activity. In the article the data obtained during the research of the Delphi group during which the experts from 12 different countries having scientific and practical work experience of work with pupils with SEN present their approaches towards what criteria should be followed in vocational counselling of pupils with SEN have been analyzed and systemized.